(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The importance of paramedics as Emergency Medical Technicians (EMTs) in Saudi Arabiacannot be overstated, as they play a crucial position in imparting immediate hospital therapy to people inemergencies. This study aims to research paramedics’ perceptions regarding the obstacles that impedetheir effectiveness in delivering superb care. Through a comprehensive analysis of the demandingsituations confronted by paramedics, inclusive of aid obstacles, schooling and training gaps, andlogistical issues, this study seeks to shed light on the barriers that hinder their ability to respondefficiently to emergencies. Understanding these boundaries is essential for growing centeredinterventions and coverage reforms, which can decorate the competencies and overall effectiveness ofparamedics in Saudi Arabia, in the end leading to stepped-forward emergency clinical services andhigher effects for patients in need.